Analysis of the sound sources of lean premixed methane–air flames. Issue 1 (23rd November 2021) - Herff, Sohel; Pausch, Konrad; Meinke, Matthias; Schröder, Wolfgang
Abstract: Two investigations on the sound generation mechanisms of lean methane–air flames are reviewed and linked. A two‐step approach is used for the analysis. First, the compressible conservation equations are solved in a large‐eddy simulation formulation to compute the acoustic source terms of the reacting fluid. Second, the acoustic source terms are used in computational aeroacoustics simulations to determine the acoustic field by solving the acoustic perturbation equations. To identify the contributions of the different source terms to the overall sound emission of the flames different source term formulations are considered in the computational aeroacoustics simulations. The results of various flames of increasing complexity are shown: harmonically excited laminar flames, a turbulent jet flame, and an unconfined and a confined swirl flame. The results show that in general the heat release source alone does not determine the acoustic emission of the flame. Only the acoustic emission of the unconfined swirl flame could be computed by the heat release source. To accurately predict the phase and the amplitude of the sound emission of the other flames the acceleration of density gradients occurring at the flame front must be included in the considered set of source terms.